Developing an Indoor Navigation Application: Identifying the Needs and Preferences of Users Who Are Visually Impaired. (September 2020) - Ponchillia, Paul E.; Jo, Song-Jae; Casey, Kim; Harding, Sheri
Introduction: This study identified users' indoor navigation concerns, prototype feature preferences, and perceptions of the relative importance and difficulty of certain building types in order to guide the development of an accurate and user-friendly indoor navigation application. Methods: Six-hundred fourteen adult volunteers who are legally blind from the 7, 000-member Sendero global positioning system (GPS) electronic discussion group completed a 27-item survey instrument using Survey Monkey Pro online. Data were analyzed using chi-square and cross tabulation statistics. Results: Participants felt points of interest were the most important type of indoor information, that ability to know their location at any time the most important application feature, and verbal output with auditory and vibrational cues, the best output mode. Airports and bus or rail transit facilities scored highest as important buildings for navigation systems, and sports arenas and airports scored highest as difficult buildings to navigate. Chi-square analyses demonstrated that gender and GPS use were related to travel confidence. In addition, GPS use was related to user age, degree of reading vision, and employment. Discussion: The findings demonstrate user preferences for an indoor wayfinding application and high-priority building types. Regardless of stated preferences, it is important to allow the user to customize the application settings. The judgments on building importance of participants provide data on which to prioritize future site development. The chi-square analyses were exploratory in nature and designed to discover possible relationships. Implications for practitioners: Vision education and rehabilitation professionals can use the findings to understand the process of accessible indoor navigation and structure lessons accordingly. Developers can improve their products. Both groups can know and understand the indoor wayfinding perceptions and opinions of more than 600 individuals who are legally blind.